Bioclimatic conditions and thermal seasons of the year in Szczecin - Mąkosza, Agnieszka. Autor (IGiPZ PAN, 2021)
Climate change is an empirical fact evidenced by subsequent IPCC reports. The observed climate change is also manifested in the altered date of occurrence and duration of the seasons in a year. Variability of thermal conditions due to climate warming will have its toll on the bioclimatic conditions. The assessment of bioclimatic conditions was conducted with the use of Universal Thermal Climate Index (UTCI). The present elaboration is based on hourly values of the following meteorological elements: air temperature, relative air humidity, wind speed and cloud cover. The meteorological data were obtained from the Institute of Meteorology and Water Management – National Research Institute (IMGW-PIB) in Szczecin and cover the period 2000-2019. Variability of bioclimatic conditions is considered per periods corresponding to thermal seasons of the year as identified by the Gumiński (1948) method on the basis of monthly air temperature values. The analysed UTCI values with respect to thermal seasons indicate that mean UTCI values in the period 2000-2019 representative for thermal summer amount to 22.6°C, thermal spring 9,9°C, thermal autumn 8.4°C, thermal winter -10.4°C, early spring -4.6°C, and early winter -7.9°C. For the periods with identified lack of thermal winter, mean UTCI value was -6.6°C. The aim of the present paper is an attempt to assess the variability of biothermal conditions as calculated using the UTCI index against the thermal seasons of the year in Szczecin.
24 cm
Keywords: UTCI; percepcja pogody; termiczne pory roku; stress termiczny